Conventional scan body vs. scan bodies with auxiliary geometric devices: an in vitro study for edentulous full-arch implant impressions - Gianfreda, Francesco; Raffone, Carlo; Martelli, Mirko; Pitino, Alberto; Caponio, Vito Carlo Alberto; Bollero, Patrizio (Frontiers in Oral Health, 2025)
AimThis study aimed to assess the effectiveness of an auxiliary geometric device (AGD) in enhancing the trueness of full-arch implant impressions. The primary metrics of interest were total surface deviation (TotRMS), centroid deviation (cRMS), and angular deviation. All these values are crucial for achieving a precise fit of implant-supported prostheses.MethodsA gypsum-based edentulous maxillary model with four multi-unit abutment replicas was prepared, replicating clinical scenarios. Control and experimental scan bodies were scanned using an intraoral scanner (Dexis 3800), and the resulting data were compared to a digital master model created with a structured light scanner (ATOS compact Scan 5M). The AGD was used to reduce positional errors during the scan process. Data were processed using Exocad and GOM Inspect Professional software, aligning scan body library files with mesh data using a best-fit algorithm. Angular, platform, and total deviations were calculated to assess positional trueness. A sample size of 20 scans per group was determined a priori, and statistical comparisons were made using Mann–Whitney U tests.ResultsThe inclusion of the AGD significantly reduced centroid root mean square (cRMS) values in all measured comparisons (p < 0.001), demonstrating enhanced trueness. The total body root mean square deviation (TotRMS) values also showed a significant reduction (p = 0.002). While overall angular deviation differences were not statistically significant (meanAGD = 0.38; meanNO = 0.39; where “NO” refers to the group without AGD), site-specific analysis revealed significant improvements at points 2.4 (p = 0.017) and 1.4 (p < 0.001). The Euclidean distance in platform deviation consistently indicated better alignment in the AGD group.ConclusionThe AGD, tested under in vitro conditions, significantly improved the trueness of full-arch implant impressions, particularly reducing c- and TotRMS values. These findings highlight the AGD's potential to enhance digital workflows in implant dentistry by mitigating positional discrepancies and ensuring greater trueness and precision. Future research should explore these findings in a clinical scenario.